Teachers' perception of the impact of the flipped learning model on student learning and engagement in high school education in Indonesia - Kusumawati, Endah Tri; Solihati, Nani; Sari, Zamah; Nurhanan, Nurhanan (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
This study aims to investigate teachers' perceptions of the impact of flipped learning on student learning and motivation in a high school in West Java. The study involved 103 teachers who have implemented flipped learning in their teaching practice. Data were collected using a questionnaire consisting of 17 statements related to teachers' perceptions of flipped learning, which were then analyzed using descriptive statistics with validity and reliability tests to examine the relationship between teachers' perceptions with gender and teaching experience. The results showed that the majority of teachers responded positively to the implementation of flipped learning, indicating a positive impact on students' motivation and readiness to be actively involved in class. However, no significant differences were found between teachers' perceptions based on gender or length of teaching experience. These findings provide important insights into the potential of flipped learning to be implemented more widely in Indonesia. The limitation of this study lies in the limited scope of the sample, so further research is needed to explore other contexts and more diverse factors. The findings can be used by teachers and policy makers to design more effective training and support programs to improve the implementation of flipped learning in Indonesia.